2017
DOI: 10.5530/jcdr.2017.4.26
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Modified Albumin (IMA) as a Novel Marker for Ischemic Heart Disease and Surrogate Marker for Other High Oxidative -Ischemic Conditions

Abstract: Aims and Objectives: To find out if ischemia modified albumin can be a novel marker in ischemic heart disease. Materials and methods: Retrospective chart-review of chest pain patients who were evaluated in the emergency departments in 2006 and 2007. Results: Total of 400 patients presented with chest pain and subsequently were evaluated in the Emergency department at two major emergency departments associated with the teaching hospital associated Mercy Catholic Medical Center; few patients were excluded due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…People with higher IMA showed longer hospitalization days and had more readmissions as compared to patients with high troponin. However, top high-level IMA did not predict negative cardiovascular events during the hospital stay, while the cTnT test predicted arrhythmia more often than the ACB test [81].…”
Section: іма As a Marker For Diseasesmentioning
confidence: 73%
“…People with higher IMA showed longer hospitalization days and had more readmissions as compared to patients with high troponin. However, top high-level IMA did not predict negative cardiovascular events during the hospital stay, while the cTnT test predicted arrhythmia more often than the ACB test [81].…”
Section: іма As a Marker For Diseasesmentioning
confidence: 73%
“…It increases in the few minutes after the start of ischemia, rises for 6-12 hours, and returns to normal in 24 hours [18]. Many studies have been published about IMA in acute cardiac and noncardiac ischemic events, however only few studies were related to COPD [7][8][9][10][11][12][13]. Can et al [19] compared serum IMA, ox-LDL (Oxidized Low-Density Lipoprotein), TAS (Total Anti-oxidant Status), and TOS (Total Oxidant Status) levels in 51 patients with stable COPD and 45 healthy cases.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological events of ischemia, including hypoxia and free oxygen radicals changed the N-terminus of albumin, and this molecule is called as IMA [6]. IMA was first discribed as a marker of myocardial ischemia, but now it has been shown that elevated in various states of noncardiac ischemia and oxidative stress conditions such as cerebrovascular diseases, inflammatory bowel diseases, chronic liver diseases, obstructive sleep apnea (OSA) and pulmonary embolism [7][8][9][10][11][12][13].Additionally, it was suggested to be a strong indicator of short-term mortality in patients with end-stage renal disease [14] and myocardial infarction with ST elevation [15].…”
mentioning
confidence: 99%
“…Ischemia-modified albumin (IMA) is also one of the novel biomarkers, and its values were altered in conditions of ischemia, inflammation, and high oxidative stress, and, therefore, it has been tested as a potential biomarker for ischemic heart disease [ 18 , 19 ]. According to some studies, IMA can predict mortality in patients with ESRD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%